Dispersion of the Yorùbá to the Americas: A Fatalist Hermeneutics of Orí in the Yorùbá Cosmos – Reading from Tutuoba: Salem’s Black Shango Slave Queen - Emmanuel Adeniyi (Yoruba Studies Review)
Studies in African Diaspora ofen privilege the transatlantic slavery, Columbus’ discovery of the New World, and African cultural codes in the Americas. To expand the scope of the studies, this article examines the metaphysical and ontological questions on the enslavement of the Yorùbá – an African ethno-nation whose members were condemned to slavery and servitude in the Americas during the inglorious transatlantic slave trade. I used metaphysical fatalism as a theoretical model to interrogate prognostications about dispersion of the Yorùbá from their matrix as expressed in their mythology. Being a predestining agent, I examined the role of orí (destiny) within the context of rigid fatalism and its textualisation in Prince Justice’s Tutuoba: Salem’s Black Shango Slave Queen. The article argues that the transatlantic enslavement of the Yorùbá is a fait accompli willed by their Supreme Deity. Tough traumatic, transatlantic slavery reworlded Yorùbá cultural codes, birthed the Atlantic sub-group of the ethno-nation, and aided the emergence of Yorùbá-centric religions in the New World.